Graphene : An Out Standing Material (Journal of Solar Energy Research Updates, 2019)
In photovoltaics, research is aiming to investigate new materials able to push the efficiency limit for solar cells towards the highest values without increasing the fabrication cost.This paper presents a review about graphene material and its potential use in all technological fields. Due to its high conductivity, transparency and amazing properties. It seems that it has an important place in the next generation of solar cells instead of silicon or thin film based solar cells, researchers found diverse applications for graphene in nanoelectronics, aviation, industry, transport, biomedecine and others.This paper present a review about the state of art about the graphene material in photovoltaic solar cells where very interesting efficiencies were recorded.